Cu-Ti-based copper alloy sheet material, method for producing same, energizing member, and heat release member

By optimizing the chemical composition and manufacturing process of Cu-Ti-based copper alloy sheets, controlling the grain diameter and residual stress indicators, the problem of unsmooth surface morphology in strict bending processing is solved, and higher bending processability and improved performance of connectors and heat-expressing components is achieved.

CN119506649APending Publication Date: 2025-02-25DOWA METALTECH CO LTD

Patent Information

Application Number
CN202410364768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-26
Filing Date
2024-03-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In strict 90° bending processing, microscopic wrinkles are easily formed on the outer peripheral surface of the bent processing part of the Cu-Ti-based copper alloy sheet, resulting in unsmooth surface shape and affecting the performance of the connector and exothermic components.

Method used

By optimizing the chemical composition and manufacturing process of copper alloy sheets, the grain diameter, GROD average value and KAM value are controlled within a specific range, ensuring the smoothness of the surface morphology of the sheet during bending processing.

Benefits of technology

Under strict bending processing conditions, the deviation between the ideal smooth curved surface profile and the actual profile of the outer peripheral surface of the bent processing part is less than 5.5 μm, which significantly reduces the problem of resin coating and improves the durability and reliability of the connector and heat-expressing components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506649A_ABST
    Figure CN119506649A_ABST
Patent Text Reader

Abstract

The invention relates to a Cu-Ti-based copper alloy sheet material, a method for producing the same, an energizing member, and a heat dissipating member. Provided is a Cu-Ti-based copper alloy sheet material having such a property that, when strict bending is performed, the actual deviation from the contour of an ideal smooth curved surface on the outer peripheral surface of a bent section is suppressed to a small extent. A copper alloy sheet material having a chemical composition containing, in mass%, 1.00-5.50% of Ti, and optionally, Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr, and a rare earth element in a total 3.00% or less range, with the remainder being Cu and unavoidable impurities, and having an average crystal grain diameter of 8.00 [mu] m or less as determined by the Area Fractionation method in which a boundary having a crystal orientation difference of 5 DEG or more is regarded as a grain boundary in a measurement of a step length of 0.05 [mu] m by EBSD, and an average crystal grain diameter of 1.00 [mu] m or less as determined by the Area Fractionation method. And the GROD average value is 7.0 DEG C or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Cu-Ti alloy sheet material having an improved surface morphology of a bent portion, a method for producing the same, and a conducting component and a heat dissipating component using the copper alloy sheet material as a raw material. The Cu-Ti alloy is a copper alloy containing about 0.5 to 6% Ti. Background Art

[0002] Among various copper alloys, Cu-Ti copper alloys have the highest strength level and good stress relaxation resistance, so they can be used as spring parts for power supply such as connectors, relays, switches, and heat dissipation parts of electronic equipment. In recent years, with the miniaturization and low-profile of electronic equipment, the demand for thin-walled connectors and heat dissipation parts used in them has also increased. For copper alloy sheets as raw materials, the balance between strength and bending workability has been increasing and becoming more important. Various studies have been conducted so far on methods to improve the strength and bending workability of Cu-Ti copper alloys.

[0003] Patent document 1 discloses a technology for optimizing the area ratio of grains whose GOS (Grain Orientation Spread) and Schmidt factor satisfy a prescribed range in a Cu-Ti copper alloy by using EBSD (electron beam backscatter diffraction), thereby improving strength and bending workability while maintaining stress relaxation resistance.

[0004] Patent Document 2 discloses a technique for obtaining a structure in which the area ratios of Brass orientation, Copper orientation, and S orientation are within a predetermined range in a Cu-Ti based copper alloy, thereby improving strength and bending workability.

[0005] Patent Document 3 discloses a technique for achieving an excellent balance between strength and ductility by controlling the morphology of a grain boundary reaction phase in a Cu-Ti based copper alloy.

[0006] Patent Document 4 discloses a technique for improving spring characteristics after bending by optimizing the conditions of solution treatment, cold rolling, and aging treatment in a Cu-Ti based copper alloy.

[0007] Patent Document 5 discloses a technique for improving high temperature fatigue resistance in a Cu-Ti based copper alloy by rationalizing the KAM value obtained by EBSD.

[0008] Patent Document 6 discloses a technique for optimizing the ratio of grains having a KAM value obtained by EBSD within a predetermined range in a Cu-Ti based copper alloy, thereby improving strength, bending workability, and fatigue properties simultaneously.

[0009] Patent Document 7 discloses a technique for improving strength and bending workability in a Cu-Ti based copper alloy by optimizing the number density of second phase particles and the extreme density of crystal grains in the range from the {111} plane to 30°.

[0010] Patent Document 8 describes a technique in which, in a Cu-Ti based copper alloy, heat treatment is performed to increase the electrical conductivity after final solution treatment, and then cold rolling and aging treatment are performed to improve properties such as strength and bendability.

[0011] Patent Document 9 discloses a technique in which, in a Cu-Ti copper alloy, a pre-heat treatment is performed after a solution treatment, and then a cold rolling and aging treatment process is performed to control the morphology of the grain boundary reaction phase, thereby improving fatigue resistance based on strict evaluation criteria.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2020-66756

[0015] Patent Document 2: Japanese Patent Application Publication No. 2013-204140

[0016] Patent Document 3: Japanese Patent Application Publication No. 2015-140477

[0017] Patent Document 4: Japanese Patent Application Publication No. 2006-265611

[0018] Patent Document 5: Japanese Patent Application Publication No. 2014-84512

[0019] Patent Document 6: Japanese Patent Application Publication No. 2016-60958

[0020] Patent Document 7: Japanese Patent Application Publication No. 2012-12631

[0021] Patent Document 8: Japanese Patent Application Publication No. 2010-261066

[0022] Patent Document 9: Japanese Patent Application Publication No. 2015-175053 Summary of the invention

[0023] Problems to be solved by the invention

[0024] If a copper alloy sheet is subjected to a strict 90° bending process, such as a BW in which the ratio of the bending radius R to the plate thickness t is about 1.0, microscopic wrinkles are formed on the outer peripheral surface of the bent portion. As long as the wrinkles are not "cracks" that cause cracking inside the wall thickness, they are generally considered not to be a problem from the perspective of strength. For example, in the evaluation of bending workability specified in the technical standard JCBA T307 of the Japan Copper Draw Association, an evaluation method based on the appearance inspection of wrinkles is also adopted. However, the surface morphology of the bent portion cannot be accurately grasped based on the size of the surface unevenness formed by the wrinkles (for example, the arithmetic mean roughness Ra based on the roughness curve). The material is stretched near the outer peripheral surface of the bent portion, so the actual surface contour deviates (deviates) from the contour of the ideal smooth curved surface. The surface morphology when the deviation is large can be regarded as a surface morphology of a so-called "large recess" formed near the top of the outer peripheral surface of the bent portion, which is sunken from the ideal smooth curved surface as a whole.

[0025] In current-carrying parts such as substrate-to-substrate (BtoB) connectors that are formed by integration with resin components, a phenomenon called "resin coating" in which resin enters the recessed portion of the outer peripheral surface of the bent portion during the resin molding process sometimes becomes a problem. At present, with the development of high-functionality electronic equipment, there is a growing demand for miniaturization and narrow pitch in current-carrying parts and heat-dissipating parts such as connectors. Among the narrow-pitch thin-walled parts, narrow-pitch connectors are easily affected by the above-mentioned resin coating, and even the previous Cu-Ti copper alloy materials intended to improve bending workability have difficulty in eliminating the problem of resin coating. To eliminate this problem, it is considered important not only to reduce the surface roughness of the bent portion (the depth of the recessed portion formed between each wrinkle), but also to make it a surface morphology with a small deviation from the contour of the ideal smooth curved surface.

[0026] An object of the present invention is to provide a Cu-Ti based copper alloy sheet material having the following properties: when subjected to a severe bending process, the deviation of the actual contour from the contour of an ideal smooth curved surface of the outer peripheral surface of the bent portion is suppressed to be small.

[0027] Means for solving problems

[0028] In order to achieve the above-mentioned object, the following inventions are disclosed in this specification.

[0029] [1] A copper alloy plate having the following chemical composition, which comprises, by mass%, Ti (titanium): 1.00-5.50%, Ag (silver): 0-0.30%, Al (aluminum): 0-3.00%, B (boron): 0-0.30%, Be (beryllium): 0-0.15%, Co (cobalt): 0-1.00%, Cr (chromium): 0-1.00%, Fe Iron: 0-1.00%, Hf (Hafnium): 0-1.00%, Mg (Magnesium): 0-1.00%, Mn (Manganese): 0-1.50%, Mo (Molybdenum): 0-1.00%, Nb (Niobium): 0-1.00%, Ni (Nickel): 0-1.50%, P (Phosphorus): 0-0.20%, S (Sulfur): 0-0.20%, Si (Silicon): 0-1 .00%, Sn (tin): 0-1.50%, Ta (tantalum): 0-1.00%, V (vanadium): 0-1.00%, Zn (zinc): 0-2.00%, Zr (zirconium): 0-1.00%, total rare earth elements: 0-3.00%, Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and total rare earth elements: 5.00% or less, the balance is Cu (copper) and unavoidable impurities, in the measurement area set in the cross section perpendicular to the rolling direction, in the measurement using EBSD (electron beam backscatter diffraction) with a step size of 0.05μm, when the boundary with a crystal orientation difference of 5° or more is regarded as a grain boundary, the Area The average grain diameter obtained by the Fraction method is less than 8.00 μm. When the average orientation of the measurement points within the same grain is set as the reference orientation of the grain, the GROD average value, which is calculated by calculating the orientation difference with the reference orientation of the grain to which each measurement point belongs and the average value for all measurement points in the measurement area, is less than 7.0°.

[0030] [2] The copper alloy sheet material according to [1] above, wherein, in the measurement using EBSD with a step size of 0.05 μm, the KAM value when a boundary with a crystal orientation difference of 5° or more is regarded as a grain boundary is 3.0° or less.

[0031] [3] The copper alloy sheet material according to [1] or [2] above, wherein the ratio MBR / t of the minimum bending radius MBR without cracking in a 90° W bending test of BW according to the technical standard of Japan Copper Alloy Association T307:2007 is 1.7 or less.

[0032] [4] The copper alloy sheet material according to any one of [1] to [3] above, wherein the tensile strength in a direction parallel to rolling is 850 MPa or more.

[0033] [5] The copper alloy sheet material according to any one of [1] to [4] above, wherein the sheet thickness is 0.02 to 0.50 mm.

[0034] [6] According to the method for manufacturing a copper alloy sheet material described in any one of [1] to [5] above, in the manufacturing process of performing a first solid solution treatment, an intermediate cold rolling, a final solid solution treatment, a finish cold rolling, a pre-aging annealing, and an aging treatment on the intermediate product sheet material in the following order, the first solid solution treatment is performed under the following conditions: after maintaining the temperature in the range of 750 to 960°C, the cooling rate from 750°C to 300°C is maintained at 3 to 30°C / s, the intermediate cold rolling is performed under the following conditions: the total rolling ratio becomes 50 to 99%, and the final solid solution treatment is performed under the following conditions: the temperature is kept at 730°C and the temperature is cooled. After maintaining the temperature in the range of 0 to 800°C, the steel is cooled at an average cooling rate from 730°C to 300°C of 100°C / s or more, and finish cold rolling is performed under the following conditions: the number of rolling passes with a reduction rate of 15% or more is 0 to 3, the total rolling pass average of the rolling load per unit width is 620 kN / m or less, and the total rolling rate is 3 to 55%. Annealing before aging is performed under the following conditions: maintaining the temperature in the range of 500 to 700°C for 25 to 600 seconds, and aging treatment is performed under the following conditions: maintaining at 300 to 500°C.

[0035] [7] The method for producing a copper alloy sheet material according to [6] above, wherein the intermediate product sheet material is a sheet material that is subjected to cold rolling after hot rolling.

[0036] [8] A current-carrying component using the copper alloy sheet material according to any one of [1] to [5] as a material.

[0037] [9] A heat dissipation component using the copper alloy sheet material according to any one of [1] to [5] as a material.

[0038] In this specification, "plate material" refers to a sheet-like metal material. Thin sheet-like metal materials are sometimes also called "foils", and such "foils" are also included in the "plate material" mentioned here. Sheet-like metal materials that are rolled into a long strip are also included in the "plate material". In addition, in this specification, the thickness of the sheet-like metal material is referred to as "plate thickness".

[0039] In the present specification, the expression “n1 to n2” indicating a numerical range means “n1 or more and n2 or less.” However, n1 and n2 are numerical values ​​satisfying n1<n2.

[0040] The average grain size, the average value of GROD (Grain Reference Orientation Deviation), and the KAM (Kernel Average Misorientation) value obtained by EBSD (Electron Beam Backscatter Diffraction) can be determined as follows.

[0041] [Method for calculating average grain diameter]

[0042] FE-SEM (field emission scanning electron microscope) was used to observe the cross section perpendicular to the rolling direction of the plate (hereinafter sometimes referred to as "LD surface".), and the EBSD (electron beam backscatter diffraction) method was used to measure the crystal orientation with a step length (measurement spacing) of 0.05 μm for the rectangular measurement area of ​​48 μm in the plate width direction and 36 μm in the plate thickness direction set in the range from 1 / 4 position to 3 / 4 position of the plate thickness. In the case where the plate thickness is thin and the 36 μm field of view cannot be ensured in the plate thickness direction, the measurement is performed for the rectangular measurement area with a plate width of 48 μm and a plate thickness direction ranging from 1 / 4 position to 3 / 4 position of the plate thickness. Using EBSD data analysis software, the boundary with a crystal orientation difference of more than 5° is regarded as the grain boundary. For all the grains located in the measurement area, the diameter is calculated using the Diameter chart, and the average value of the grain diameter is calculated using the Area Fraction method. For grains where part of the grains overflow from the boundary of the measurement area, the area of ​​the part existing in the measurement area is directly used for the calculation of the average grain diameter. This operation was performed for the measurement areas of 5 randomly selected, non-repeating fields of view, and the arithmetic mean of the average values ​​of the grain diameters obtained in the 5 fields of view was taken as the average grain diameter (μm). Furthermore, the twin boundaries ({111} / Σ3 corresponding to grain boundaries, {110} / Σ9 corresponding to grain boundaries) were ignored and not considered as grain boundaries, and the average grain diameter was calculated.

[0043] The so-called "plate thickness 1 / 4 position" refers to the position in the plate thickness direction that is t / 4 (mm) away from a rolling surface when the plate thickness is t (mm). Similarly, the so-called "plate thickness 3 / 4 position" refers to the position in the plate thickness direction that is 3t / 4 (mm) away from the above-mentioned rolling surface.

[0044] [How to calculate the GROD average value]

[0045] Based on the above EBSD measurement data measured on the LD surface with a step size (measurement spacing) of 0.05μm, EBSD data analysis software was used to regard boundaries with an orientation difference of more than 5° as grain boundaries (also including twin boundaries ({111} / Σ3 corresponding to grain boundaries, {110} / Σ9 corresponding to grain boundaries)), and the average orientation of the measurement points within the same grain as the reference orientation of the grain. For all measurement points in the measurement area, the orientation difference GROD (Grain Reference Orientation Deviation-Angle) value (°) with respect to the reference orientation of the grain to which the point belongs was calculated, and their average value was taken as the GROD average value (°).

[0046] [How to calculate KAM value]

[0047] Based on the above EBSD measurement data measured on the LD surface with a step length (measurement spacing) of 0.05μm, the KAM (Kernel Average Misorientation) value when the boundary (including the twin boundary) with an orientation difference of 5° or more is regarded as a grain boundary is calculated using EBSD data analysis software. For this KAM value, for the electron beam irradiation points configured at a spacing of 0.05μm, the crystal orientation difference between all adjacent points (hereinafter referred to as "adjacent point orientation difference") is measured, and only the measured values ​​of the adjacent point orientation difference of less than 5° are selected, and their average value is calculated, and the KAM value is equivalent to the average value.

[0048] The BW in the above 90° W bending test is an abbreviation for “Bad Way”, which means that the bending axis is parallel to the rolling direction.

[0049] The reduction ratio (%) in a certain rolling pass is determined by the following formula (1).

[0050] Pressing rate (%) = 100 × (t0-t1) / t0…(1)

[0051] t0: Plate thickness before this rolling pass (mm)

[0052] t1: Plate thickness at the end of this rolling pass (mm)

[0053] The total rolling reduction (%) in a certain rolling process is determined by the following formula (2).

[0054] Total rolling rate (%) = 100 × (h0-h1) / h0…(2)

[0055] h0: Plate thickness before the first rolling pass in the rolling process (mm)

[0056] h1: Plate thickness at the end of the final rolling pass of the rolling process (mm)

[0057] Effects of the Invention

[0058] According to the Cu-Ti copper alloy sheet material of the present invention, when a strict bending process is performed, a surface morphology with a small deviation from the contour of an ideal smooth curved surface of the outer peripheral surface of the bent portion can be obtained. As a result, for example, the following effects can be expected: the problem of resin coating in a narrow-pitch substrate-to-substrate (BtoB) connector is significantly alleviated. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 A photograph in lieu of a drawing illustrating the appearance of the curved outer peripheral surface of a conventional material (Comparative Example No. 43).

[0060] Figure 2 As an example for Figure 1 Figure 2. Plot of the height profile measured on the surface of a surface.

[0061] Figure 3 For the general Figure 2 A diagram showing an enlarged view near the top of the contour.

[0062] Figure 4 A photograph in lieu of a drawing illustrating the appearance of the curved outer peripheral surface of the material of the present invention (Inventive Example No. 1).

[0063] Figure 5 As an example for Figure 4 Figure 2. Plot of the height profile measured on the surface of a surface.

[0064] Figure 6 For the general Figure 5 A diagram showing an enlarged view near the top of the contour. DETAILED DESCRIPTION

[0065] [Chemical composition]

[0066] Unless otherwise specified, "%" regarding alloy components below means "mass %".

[0067] Ti brings about the formation of a Ti modulation structure based on spinodal decomposition and the formation of fine second phase particles based on precipitation, and is an element that contributes to the strength increase of the Cu-Ti copper alloy of the present invention. In addition, it also contributes to the reduction of stress relaxation resistance. In order to fully exert these effects, a Ti content of more than 1.00% is ensured. From the viewpoint of precipitation strengthening, the Ti content is more preferably more than 1.50%, and further preferably more than 2.50%. Excessive Ti becomes the main factor for the reduction of hot workability and cold workability, and also becomes the main factor for the reduction of bending workability, so the Ti content is set to less than 5.50%. It can be managed to be less than 5.00%, less than 4.50%, or less than 4.00%.

[0068] Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and rare earth elements are optional elements. One or more of these can be contained as needed. For example, Al is effective in suppressing the formation of coarse precipitates in Cu-Ti copper alloys and is also effective in reducing the density (specific gravity) of copper alloys. Ni, Co, Fe, and Nb form intermetallic compounds with Ti, which contribute to the improvement of strength. In addition, the intermetallic compounds of these elements suppress the coarsening of grains, so that solid solution treatment in a higher temperature range can be performed in the manufacture of copper alloy sheets, which is beneficial in making Ti fully solid-dissolved. Ag and Sn have a solid solution strengthening effect and an improvement in stress relaxation resistance. In addition to improving weldability and strength, Zn is also effective in improving castability. Mg has an improvement in stress relaxation resistance and a desulfurization effect. Si can form a compound with Ti, which contributes to pinning during recrystallization in the manufacture of copper alloy sheets and can miniaturize the grain diameter. Cr and Zr are effective for dispersion strengthening and suppression of grain coarsening. Mn and V easily form high melting point compounds with S and the like, and B and P have a refining effect on the casting structure, and each can contribute to improvement of hot workability.

[0069] Rare earth elements (REM) are Sc (scandium), Y (yttrium), and lanthanide elements (excluding Pm (promethium)) of the third group of the periodic table. The inclusion of rare earth elements is effective for grain refinement and dispersion of precipitates. As a source of rare earth elements, misch metal (a mixture of rare earth elements) can be used.

[0070] The content of the above optional elements can be set to the range of Ag: 0-0.30%, Al: 0-3.00%, B: 0-0.30%, Be: 0-0.15%, Co: 0-1.00%, Cr: 0-1.00%, Fe: 0-1.00%, Hf: 0-1.00%, Mg: 0-1.00%, Mn: 0-1.50%, Mo: 0-1.00%, Nb: 0-1.00%, Ni: 0-1.50%, P: 0-0.20%, S: 0-0.20%, Si: 0-1.00%, Sn: 0-1.50%, Ta: 0-1.00, V: 0-1.00%, Zn: 0-2.00%, Zr: 0-1.00%, and the total of rare earth elements: 0-3.00%. For rare earth elements, for example, there can be listed a range including one or more selected from La (lanthanum): less than 2.00%, Ce (cerium): less than 1.80%, Pr (praseodymium): less than 0.30%, Nd (neodymium): less than 0.80%, Sm (samarium): less than 2.50%, and Y (yttrium): less than 2.50%, and the total content of rare earth elements is less than 3.00%.

[0071] In addition, the contents of the above optional elements can be managed in the range of Ag: 0 to 0.20%, Al: 0 to 2.80%, B: 0 to 0.10%, Be: 0 to 0.08%, Co: 0 to 0.70%, Cr: 0 to 0.10%, Fe: 0 to 0.80%, Hf: 0 to 0.10%, Mg: 0 to 0.70%, Mn: 0 to 0.70%, Mo: 0 to 0.10%, Nb: 0 to 0.80%, Ni: 0 to 0.80%, P: 0 to 0.08%, S: 0 to 0.05%, Si: 0 to 0.20%, Sn: 0 to 1.20%, Ta: 0 to 0.10%, V: 0 to 0.10%, Zn: 0 to 0.50%, Zr: 0 to 0.20%, and the total of rare earth elements: 0 to 2.00%. In this case, further considering the economy and manufacturability, a more preferred rare earth element content range can be, for example, a range including one or more selected from La: less than 0.50%, Ce: less than 1.00%, Pr: less than 0.15%, Nd: less than 0.40%, Sm: less than 1.80%, and Y: less than 1.00%, and the total content of rare earth elements is less than 1.80%.

[0072] In addition, the contents of the above optional elements can be managed in the range of Ag: 0 to 0.10%, Al: 0 to 2.60%, B: 0 to 0.03%, Be: 0 to 0.04%, Co: 0 to 0.35%, Cr: 0 to 0.02%, Fe: 0 to 0.60%, Hf: 0 to 0.01%, Mg: 0 to 0.40%, Mn: 0 to 0.40%, Mo: 0 to 0.01%, Nb: 0 to 0.50%, Ni: 0 to 0.30%, P: 0 to 0.03%, S: 0 to 0.015%, Si: 0 to 0.08%, Sn: 0 to 0.60%, Ta: 0 to 0.01%, V: 0 to 0.03%, Zn: 0 to 0.10%, Zr: 0 to 0.02%, and the total of rare earth elements: 0 to 0.90%. In this case, further considering the economy and manufacturability, a more preferred rare earth element content range can be, for example, a range including one or more selected from La: less than 0.30%, Ce: less than 0.50%, Pr: less than 0.05%, Nd: less than 0.20%, Sm: less than 0.80%, and Y: less than 0.60%, and the total content of rare earth elements is less than 0.80%.

[0073] Regarding the total content of the optional elements Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and rare earth elements, from the viewpoint of the cost of the copper alloy, it is preferably 5.00% or less, more preferably 3.00% or less, further preferably 2.00% or less, and can be managed to be 1.60% or less.

[0074] For elements other than the above, it is permitted to contain elements other than the above within a range that does not hinder the purpose of the present invention (imparting the characteristic of suppressing the deviation between the ideal smooth curved surface profile of the outer peripheral surface of the bent portion and the actual profile). Specifically, the total content of elements other than Ti, Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr, rare earth elements, and Cu (hereinafter sometimes referred to as "non-specified elements") is preferably 0.50% or less, and can be managed to be less than 0.10%. The content of non-specified elements can be grasped by, for example, quantifying substantially all elements that can be contained in the copper alloy sheet using the following analysis method.

[0075] (Example of quantitative method for alloy elements)

[0076] O (oxygen) and N (nitrogen) are quantified using an oxygen, nitrogen, and hydrogen analyzer (e.g., ONH-836 manufactured by LECO), H (hydrogen) is quantified using a hydrogen analyzer (e.g., EMGA-921 manufactured by Horiba, Ltd.), C (carbon) and S (sulfur) are quantified using a carbon-sulfur analyzer (e.g., CS844 manufactured by LECO), elements of the 2nd to 6th periods (excluding C, N, O, Group 17 elements, Group 18 elements, Tc (technetium), Po (polonium), and Pm (promethium)) are quantified using ICP-MS (e.g., 7900 manufactured by Agilent), and F (fluorine), Cl (chlorine), and Br (bromine) are quantified using a combustion-ion chromatograph (e.g., DIONEX ICS-1600 manufactured by Thermo Scientific).

[0077] Regarding the chemical composition of the copper alloy sheet material according to the present invention, in addition to being limited to "consisting of Ti, the above-mentioned optional elements (including the case where the total is 0 mass%), the remainder Cu and inevitable impurities", it can also be limited to "consisting of Ti, the above-mentioned optional elements (including the case where the total is 0 mass%), the above-mentioned unspecified elements (including the case where the total is 0%), and the remainder Cu".

[0078] [Average grain diameter]

[0079] The copper alloy sheet material of the present invention is characterized in that, in the measurement of the measurement area set in the cross section (LD plane) perpendicular to the rolling direction with an EBSD step size of 0.05 μm, the average grain diameter obtained by the Area Fraction method when the boundary with a crystal orientation difference of more than 5° is regarded as the grain boundary is 8.00 μm or less. If this feature is not met, it is difficult to stably obtain the appropriate surface morphology in the strict bending process of BW. The above-mentioned average grain diameter is more preferably less than 5.50 μm, further preferably less than 4.00 μm, and can also be adjusted to less than 2.00 μm. There is no special limitation on the lower limit of the average grain diameter. Excessive refinement becomes the main factor that causes the increase in the process load of copper alloy sheet manufacturing, so it can usually be controlled in the range of more than 0.50 μm.

[0080] [GROD average]

[0081] The copper alloy sheet of the present invention is characterized in that, in the above-mentioned EBSD measurement, the GROD average value when the boundary (including the twin crystal boundary) with a crystal orientation difference of 5° or more is regarded as the grain boundary is 7.0° or less. The GROD average value is equivalent to the value of the average value calculated by finding the orientation difference with the reference orientation of the grain to which each measurement point belongs for all measurement points in the measurement area. Among them, as the reference orientation of each grain, the average orientation of the measurement points based on the same grain is adopted. The GROD average value becomes an indicator of the extent of the residual stress accumulated inside each grain in the sheet as a whole. According to the research of the inventors, it can be seen that the GROD average value has a great influence on the morphology of the outer peripheral surface of the bending processing part. In order to stably obtain the appropriate surface morphology in the strict bending process of BW, it is extremely effective to have a GROD average value of 7.0° or less. It is more preferably 6.0° or less, and further preferably 3.7° or less. The lower limit of the GROD average value is not particularly limited, but excessive reduction of residual stress may lead to an increase in the process load of copper alloy sheet production. Therefore, it is usually controlled within a range of 1.0° or more.

[0082] [KAM value]

[0083] The KAM value is an indicator that provides clues to the extent to which local lattice distortion (residual stress) exists in the entire sheet. In order to obtain appropriate surface morphology in the strict bending process of BW, in the above-mentioned EBSD measurement with a measurement step size set to a micro size such as 0.05μm, the KAM value when the boundary with a crystal orientation difference of more than 5° (including twin crystal boundaries) is regarded as a grain boundary is preferably 3.0° or less. It is more preferably less than 2.5°, and further preferably less than 2.0°. However, even if the KAM value meets this feature, if the GROD average value is not controlled within the above-specified range, the appropriate surface morphology cannot be stably achieved in the strict bending process of BW. There is no special limitation on the lower limit of the KAM value. Excessive reduction of residual stress becomes the main factor that leads to an increase in the process load of copper alloy sheet manufacturing, so it can usually be controlled in the range of more than 0.3°.

[0084] [Maximum deviation from the ideal smooth curved surface of the outer periphery of the bent portion]

[0085] In the 90°W bending test of BW described later, the maximum deviation from the ideal smooth curved surface of the outer periphery of the bent portion is preferably 5.5 μm or less. A plate having a maximum deviation of 4.0 μm or less, or further 3.0 μm or less, can also be obtained. In addition, it is difficult to make the maximum deviation completely zero, and it is usually 0.1 μm or more. The details of the method for obtaining the maximum deviation will be described in the examples.

[0086] [MBR / t using 90°W bending test]

[0087] In the copper alloy sheet of the present invention, the ratio MBR / t of the minimum bending radius MBR without cracking to the plate thickness t in the 90° W bending test of BW according to the technical standard of the Japan Copper Bending Association JCBA T307:2007 is preferably 1.7 or less, and more preferably 1.3 or less. MBR / t of 0 can also be obtained. In addition, MBR / t in this test is an indicator for evaluating bending workability in the past, indicating to what extent strict bending does not cause cracks. For Cu-Ti copper alloy sheets whose chemical composition, average grain size, and GROD average value are not controlled within the above-mentioned appropriate ranges, even if the bending workability based on MBR / t is good, it is difficult to stably achieve a surface morphology with a small deviation from the ideal smooth surface in the strict bending process of BW.

[0088] JCBA T307:2007 states that "This standard is applicable to the evaluation of the bending workability of copper and copper alloy thin strips with a thickness of 0.1 mm or more and 0.8 mm or less." According to the inventor's research, it has been confirmed that the W bending test according to this standard can also be used to evaluate the bending workability of Cu-Ti copper alloy sheets with a thickness of less than 0.1 mm. Therefore, in the present invention, the W bending test method of BW shown in JCBA T307:2007 is also extended to the case where the thickness is less than 0.1 mm (for example, 0.02 mm or more and less than 0.1 mm) and directly applied. The width of the test piece can be, for example, 1 mm.

[0089] [Tensile strength]

[0090] The tensile strength of the copper alloy sheet of the present invention in the rolling parallel direction (LD) is preferably 850 MPa or more, more preferably 900 MPa or more. The tensile strength in the rolling direction can also be adjusted to a strength level of 1000 MPa or more. There is no particular restriction on the upper limit of the tensile strength, for example, it can be adjusted within a range of less than 1500 MPa, or within a range of less than 1300 MPa.

[0091] [Electrical conductivity]

[0092] In the application of the copper alloy sheet material of the present invention, it is preferable to ensure an electrical conductivity of 8% IACS or more (for example, 8% IACS or more and 25% IACS or less).

[0093] [Manufacturing method]

[0094] The copper alloy sheet material described above can be produced, for example, by the following production process.

[0095] Melting and casting → heating of cast pieces → hot working → rough cold rolling → first solution treatment → intermediate cold rolling → final solution treatment → finishing cold rolling → annealing before aging → aging treatment → (cold rolling after aging → low temperature annealing)

[0096] The above steps in brackets can be performed as needed. Although not described in the above steps, face grinding can be performed as needed after hot working, and pickling, grinding, or further degreasing can be performed as needed after each heat treatment. The above steps are described below.

[0097] [Melting and Casting]

[0098] The casting of the chemical composition specified in the present invention can be produced using a crucible furnace, etc. In order to prevent oxidation of easily oxidizable elements such as Ti, the casting can be carried out in an inert gas atmosphere or a vacuum melting furnace.

[0099] [Casting Slab Heating]

[0100] The casting piece can be heated before hot working by, for example, maintaining the casting piece at 900 to 1000° C. for 0.5 to 5 hours.

[0101] [Hot working, rough cold rolling]

[0102] There is no particular limitation on the method of hot working. Usually, hot rolling and electric forging are used. In the case of hot rolling, the total hot rolling rate can be, for example, 60 to 99%. After the hot working is completed, it is preferably quenched by water cooling or the like. Then, cold rolling is performed. Cold rolling at this stage is referred to as "rough cold rolling" in this specification. The rolling rate in rough cold rolling can be, for example, 50 to 99%. In this way, an intermediate product sheet for the first solution treatment can be obtained.

[0103] [First solution treatment]

[0104] For the intermediate product sheet mentioned above, the first solution treatment is implemented. In this solution treatment, the strain introduced in the rough cold rolling is used as the driving force to recrystallize it, so that the coarse grain boundary reaction type precipitates and granular precipitates generated in casting and hot working are fully dissolved. If the solid solution of the precipitates is insufficient at this stage, it is difficult to fully generate fine precipitates that contribute to strength in the aging treatment process. The heating and holding temperature of the first solution treatment is set in a temperature range of 750 to 960°C, and more preferably in a temperature range of 780 to 880°C. If the heating and holding temperature is as high as more than 960°C, sometimes the grains become excessively large. The holding time in the heating and holding temperature range can be set in the range of, for example, 10 to 600 seconds. In the cooling process after heating and holding, the temperature range where precipitates are easily generated is not quenching, and it is important to control the cooling rate to be relatively slow. Specifically, from 750°C to 300°C, the cooling rate is maintained at 3 to 30°C / s for cooling. As a result, coarse precipitates are generated during the cooling process to a degree that does not contribute to precipitation strengthening. The fixing effect brought by the coarse precipitates plays a role in each heating process described later, inhibiting the growth of grains and ultimately enabling grain refinement. Furthermore, if water cooling is performed, the cooling rate usually exceeds 100°C / s, so water cooling is not used in this process.

[0105] [Intermediate cold rolling]

[0106] The cold rolling performed on the material that has completed the first solution treatment is called intermediate cold rolling. In the intermediate cold rolling, in addition to reducing the plate thickness, the purpose is also to introduce strain. If the introduction of strain is insufficient, the nucleation site for recrystallization cannot be fully ensured in the final solution treatment that follows, and the refinement of the grains becomes difficult. In the intermediate cold rolling, the total rolling ratio is set to be above 50%. It is more effective to set the total rolling ratio to be above 85%, and to be above 90% more effective. There is no particular restriction on the upper limit of the total rolling ratio, and it can usually be set to a range below 99% according to the capacity of the cold rolling mill.

[0107] [Final solution treatment]

[0108] In the material that has completed the intermediate cold rolling, the precipitates have been fully dissolved, and strain has been introduced into the crystallization of the matrix (metal substrate). For the plate in such a state of organization, the final solution treatment is implemented. In the final solution treatment, the strain introduced in the intermediate cold rolling is used to generate new recrystallization from many places to achieve grain refinement. The main purpose is not the solutionization of the precipitates, but the grain refinement brought about by recrystallization, so the upper limit of the allowable heating temperature is reduced compared with the first solution treatment. Specifically, it is carried out under the condition of maintaining the temperature range of 730 to 800°C. The holding time in the heating and holding temperature range can be set in the range of 10 to 600 seconds, for example. As for the coarse precipitates used to exert the fixing effect, the coarse precipitates generated during the cooling process of the above-mentioned first solution treatment are already fully present. If a large number of precipitates are newly generated during the cooling process of the final solution treatment, it will have an adverse effect on strength and bending workability. Therefore, in the final solution treatment, cooling is performed at a fast cooling rate in a manner that does not produce new precipitation as much as possible. Specifically, cooling is performed so that the average cooling rate from 730°C to 300°C becomes 100°C / s or more. For example, water cooling of a plate out of a furnace to below 300°C usually corresponds to cooling with an average cooling rate of 100°C / s or more.

[0109] [Fine cold rolling]

[0110] The cold rolling performed on the material after the final solution treatment is called "finish cold rolling". In the finish cold rolling, while reducing the plate thickness, the microscopic grain size determined by the above-mentioned EBSD measurement is refined. In the case of not performing the "cold rolling after aging" described later, the plate thickness after the finish cold rolling becomes the plate thickness of the final product plate. In the finish cold rolling, it is important to reduce the plate thickness while considering that the strain imparted to the crystallization does not become excessively large, and careful control is required. Specifically, the finish cold rolling is performed under the conditions that the number of rolling passes with a reduction rate of more than 15% is more than 0 and less than 3, the total rolling passes of the rolling load per unit width is an average of less than 620 kN / m, and the total rolling rate is 3 to 55%. The rolling load per unit width is the value obtained by dividing the rolling load (kN) by the plate width (m).

[0111] [Annealing before aging]

[0112] In the above-mentioned fine cold rolling, control is performed so that the introduction of strain is reduced, but in order to refine the grains, a certain degree of strain is inevitably introduced. In this state, it is not sufficient to fully give the properties that make the morphology of the outer peripheral surface of the bent portion close to the profile of the ideal smooth curved surface. Therefore, annealing is performed before aging treatment to further reduce the strain within the range where recrystallization does not occur. This annealing is called "pre-aging annealing". In the pre-aging annealing, the condition of maintaining the temperature in the range of 500 to 700°C for 25 to 600 seconds can be adopted.

[0113] [Aging Processing]

[0114] Secondly, an aging treatment is performed. The aging treatment can be performed under normal conditions so that fine precipitates are fully generated. Specifically, the aging temperature can be set in a temperature range of 300 to 500°C. The holding time in this temperature range can be adjusted in the range of 1 to 24 hours, for example. The main purpose of the pre-aging annealing is to reduce strain, and the main purpose of the aging treatment is to generate fine precipitates. The temperature of the aging treatment can usually be set to be lower than the temperature of the pre-aging annealing, for example, about 100 to 300°C.

[0115] [Cold rolling after aging]

[0116] If further final plate thickness adjustment is required, a slight cold rolling may be performed after the aging treatment. This cold rolling is referred to as "post-aging cold rolling." In the post-aging cold rolling, the total rolling reduction is preferably within a range of 20% or less.

[0117] [Low temperature annealing]

[0118] When cold rolling is performed after aging, low temperature annealing is finally performed to reduce strain. For example, the low temperature annealing can be performed under the condition of holding at 350 to 500° C. for 10 to 600 seconds.

[0119] [Electrical parts, heat dissipating parts]

[0120] As described above, a Cu-Ti copper alloy sheet material having a surface morphology with a small deviation from the contour of an ideal smooth curved surface of the outer peripheral surface of the bent portion can be obtained when a strict bending process is performed. The final sheet thickness can be set to, for example, a range of 0.02 to 0.50 mm. In the current-carrying parts and heat-dissipating parts formed by a process including bending using the sheet material, the durability reliability of the bent portion is improved.

[0121] Example

[0122] The copper alloy having the chemical composition shown in Table 1 was melted and cast. The obtained cast piece (thickness 50 mm) was heated at 950°C for 1 hour, hot rolled to the plate thickness shown in Table 2, and water cooled. After hot rolling, the surface oxide layer was removed by mechanical grinding (face grinding), and each hot-rolled material was cold rolled to the plate thickness shown in the "rough cold rolling" column of Table 2 to obtain an intermediate product plate.

[0123] Furthermore, for the analysis samples taken out from the ingots, elemental analysis was carried out using the method described in the above-mentioned "Examples of Quantitative Methods for Alloy Elements". The results showed that in all examples, the total content of elements other than Ti, Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr, rare earth elements, and Cu was less than 0.10%.

[0124] For the intermediate product sheet materials described above, the first solution treatment, intermediate cold rolling, final solution treatment, finish cold rolling, pre-aging annealing, and aging treatment were sequentially performed under the conditions shown in Tables 2, 3, and 4, and test materials for various evaluations described later were obtained. Among them, the process indicated by "-" (hyphen) in Tables 2, 3, and 4 means that it was not performed. In No. 14, 20, 45, 46, and 53, post-aging cold rolling and low-temperature annealing were performed under the conditions shown in Table 4 after the aging treatment. In No. 44 and 46, cold rolling was performed under the conditions shown in Table 4 before the aging treatment. In No. 55, since cracks occurred in the material during hot rolling, the subsequent processes were suspended.

[0125] In the final solution treatment, except for the example shown as water cooling in Table 3, the cooling rate was controlled by gas cooling. The aging treatment was carried out in a nitrogen atmosphere using a batch heat treatment furnace. In the example where low-temperature annealing was implemented, the plate after low-temperature annealing was used as the test material, and in the other examples, the plate after aging treatment was used as the test material. The plate thickness of the test material is shown in the "Final Plate Thickness" column in Table 4. For each test material, the following examination was carried out.

[0126] (Average grain diameter)

[0127] For the cross section (LD surface) perpendicular to the rolling direction of the sample taken from the test material, a cross-section polisher (IB-19530CP manufactured by JEOL Ltd.) was used to process it with an acceleration voltage of 4kV, thereby preparing a sample surface for EBSD (electron beam backscatter diffraction) measurement. The sample surface was observed using FE-SEM (JSM-7200F manufactured by JEOL Ltd.) under the conditions of an acceleration voltage of 15kV and a magnification of 2500 times. For a rectangular measurement area of ​​48μm in the plate width direction and 36μm in the plate thickness direction set within the range from the 1 / 4 position to the 3 / 4 position of the plate thickness, an EBSD device (Symmetry manufactured by Oxford Instruments) set in FE-SEM was used to collect crystal orientation data using the EBSD method with a step length of 0.05μm. Based on the crystal orientation data measured for the measurement area of ​​5 non-repeating fields of view, the average grain diameter based on the Area Fraction method was obtained according to the above-mentioned "Method for obtaining the average grain diameter". As EBSD data analysis software, OIM-Analysis 7.3.1 manufactured by TSL Solutions Co., Ltd. was used (the same applies to calculation of the GROD average value and KAM value described later).

[0128] (GROD average)

[0129] Based on the crystal orientation data collected by the above-mentioned EBSD method, the GROD average value was calculated according to the above-mentioned “method for calculating the GROD average value”.

[0130] (KAM value)

[0131] Based on the crystal orientation data collected by the above-mentioned EBSD method, the KAM value was calculated according to the above-mentioned “method for calculating the KAM value”.

[0132] (Maximum deviation from the ideal smooth curved surface of the outer periphery of the bent portion)

[0133] A test piece 30 mm long and 0.3 mm wide was cut from the test material in such a way that the longitudinal direction of the test piece was aligned with the rolling direction at right angles to the surface of the test material. A 90°W bending test with a ratio of bending radius R (mm) to plate thickness t (mm) R / t of 1.0 was conducted according to the technical standard of Japan Copper and Copper Bending Association JCBA T307:2007. A laser microscope (LEXT OLS4000, manufactured by Olympus Corporation) was used to observe the curved peripheral surface of the curved portion formed on the test piece, and the height profile of the peripheral surface of the bent portion was measured when scanning in a direction at right angles to the width direction of the test piece. A 50x objective lens was used for the observation. The height direction of the profile is the direction corresponding to the travel direction of the fixture during the bending process. As for the specific measurement method, Figure 1 to Figure 3 Take this as an example to illustrate.

[0134] exist Figure 1 4 shows an appearance photograph of the bent outer peripheral surface of Comparative Example No. 43, which is a conventional material, viewed in a direction corresponding to the traveling direction of the jig during bending. The horizontal direction of the photograph is the width direction of the test piece (i.e., the direction parallel to the bending axis), and the straight line shown in the photograph and parallel to the vertical direction of the photograph is the profile measurement line.

[0135] exist Figure 2 For example, Figure 1 The height profile measured on the surface. In the measured profile (solid line), there are more irregular bumps from the vertex (the highest point in height) to a depth of about 15 μm. Therefore, in the data of the measured profile curve, the data of the portion of the depth from the vertex in the range of 15 to 25 μm is used to create a polynomial approximation curve (quadratic function). At this time, the measurement position ( Figure 2 The polynomial approximation curve was created by least square method using the data of the horizontal axis of the bending part. The polynomial approximation curve obtained in this way is regarded as the "ideal profile" and the cross-sectional curve of the ideal smooth surface of the outer periphery of the bending part. Figure 2 The ideal contour is shown by a dotted line in FIG. 1. It can be seen that the actual curved peripheral surface has a sunken surface near the top.

[0136] exist Figure 3 Lieutenant General Figure 2 The top of the outline is enlarged. Figure 3 The maximum value (μm) of the height direction distance between the ideal profile (dashed line) and the measured profile (solid line) at the horizontal axis position is defined as the "maximum deviation". In the example of this figure, the maximum deviation is 8.3μm.

[0137] For the determination of the maximum deviation, for one test piece, the maximum deviation is measured using five randomly set measurement lines, and the maximum value of the five maximum deviation values ​​is taken as the maximum deviation of the test piece. With the number of tests n = 3, the maximum deviation of three test pieces is determined, and the average value of the maximum deviation measurement values ​​of the three test pieces is taken as the result value of the maximum deviation of the test material. Figure 2 , Figure 3 In No. 43 shown as an example, the maximum deviation result value was found to be 7.8 μm.

[0138] The maximum deviation of the bending test piece of each test material was measured by the above method. A Cu-Ti copper alloy sheet material having a maximum deviation of 6.0 μm or less according to this test method was evaluated as having a property of significantly improving the surface morphology of the bent portion compared with the conventional method.

[0139] exist Figure 4 The following is a photograph of the outer peripheral surface of the bending of Example No. 1 of the present invention viewed in a direction corresponding to the direction of travel of the jig during bending. The horizontal direction of the photograph is the width direction of the test piece (i.e., the direction parallel to the bending axis), and the straight line shown in the photograph and parallel to the vertical direction of the photograph is the contour measurement line. Figure 5 For example, Figure 4 The height profile of the surface is measured. Figure 6 Lieutenant General Figure 5 An enlarged representation near the top of the contour is shown. Figure 6 The vertical axis is relative to the above Figure 3 The maximum deviation in this example is 1.8 μm. Figure 5 , Figure 6 In No. 1 shown as an example, the maximum deviation result value was found to be 1.8 μm.

[0140] (MBR / t obtained using 90°W bending test)

[0141] Independently from the evaluation of the maximum deviation described above, the bending workability was evaluated by a conventional bending test as follows. The ratio of the minimum bending radius MBR and the plate thickness t, MBR / t, which does not cause cracks in the W bending test using BW according to the technical standard of the Japan Copper and Copper Association JCBA T307:2007, was calculated. The test piece size was 30 mm in the length of the surface of the test material in the direction perpendicular to rolling and 1.0 mm in the rolling direction (width of the test piece). The determination of the presence or absence of cracks on the surface of the bent portion was carried out in accordance with JCBA T307:2007. For samples judged as "wrinkles: large" in the appearance observation of the surface of the bent portion, a sample was prepared by cutting vertically in the direction of the bending axis for the deepest part of the wrinkles, and the polished cross-section was observed using an optical microscope to confirm whether cracks that develop into the inside of the plate thickness have occurred. In the case where such cracks have not occurred, it was determined that "no cracks were found". Considering the use of the material of the present invention, as long as the MBR / t according to this test is 1.70 or less, it is evaluated to have good bending workability.

[0142] (Tensile Strength)

[0143] Tensile test pieces (JIS No. 5) in the rolling direction were taken out from each test material, and the tensile test was carried out according to JIS Z2241 with the test number n = 3 to measure the tensile strength. The average value of n = 3 was taken as the result value of the test material.

[0144] (Conductivity)

[0145] The electrical conductivity of each test material was measured using the double bridge average cross-sectional area method in accordance with JIS H0505.

[0146] The above results are shown in Table 5.

[0147]

Table 1

[0148] Table 1

[0149]

[0150] Underline: outside the scope of the present invention

[0151]

Table 2

[0152] Table 2

[0153]

[0154] Underline: outside the scope of the present invention

[0155]

Table 3

[0156] Table 3

[0157]

[0158] Underline: outside the scope of the present invention

[0159]

Table 4

[0160] Table 4

[0161]

[0162] Underline: outside the scope of the present invention

[0163]

Table 5

[0164] Table 5

[0165]

[0166] Underline: outside the scope of the present invention

[0167] The examples of the present invention that strictly control the chemical composition and the manufacturing conditions of the plate within the above-mentioned appropriate range all show an organizational state in which the average grain size and the GROD average value are within the range specified by the present invention, and have a maximum deviation from the ideal smooth surface of the outer periphery of the bending processing part (hereinafter referred to as "maximum deviation") of less than 6.0 μm. In addition, their bending workability in the usual evaluation method is also good, and their strength and conductivity are also good.

[0168] In the comparative example No. 41, the temperature of the first solution treatment was too high, so the grain size became larger. In addition, the number of passes with a reduction ratio of 15% or more, the average rolling load per unit width, and the total rolling ratio in the finish cold rolling were high, so the GROD average value increased. As a result, the improvement of the bending workability was insufficient, and the maximum deviation became larger.

[0169] No.42 Since the temperature of the final solution treatment is high, the precipitates that play a fixing effect generated during the cooling process of the first solution treatment dissolve, and the grain size becomes very large. When the grain size is very large, the GROD average value tends to increase. As a result, the improvement of the bending workability is insufficient, and the maximum deviation becomes very large.

[0170] Since No. 43 did not undergo annealing before aging, the GROD average value increased and the maximum deviation was large.

[0171] In No. 44, the temperature of the final solution treatment was too high, so the grain size became large, and in addition, the GROD average value increased because the cold rolling before aging was performed. As a result, the maximum deviation was large.

[0172] In No. 45, the final solution treatment temperature was high and the finish cold rolling was not performed, so the grain size became larger. In addition, the annealing temperature before aging was low, so the GROD average value increased. As a result, the maximum deviation was large.

[0173] No. 46 did not undergo the first solution treatment, so the precipitates that exerted the fixing effect were insufficient, and the grain size was large because the temperature of the final solution treatment was high. In addition, the GROD average value increased because the cold rolling before aging was performed. As a result, the improvement of the bending workability was insufficient, and the maximum deviation became larger.

[0174] Since the final solution treatment was not performed in No. 47, the grain size became larger and the maximum deviation was larger.

[0175] In No. 48, the total rolling reduction in the finish cold rolling was high, so the GROD average value was high. As a result, the improvement in the bending workability was insufficient, and the maximum deviation became large.

[0176] In No. 49, the first solution treatment was performed at a high temperature and the cooling rate was also high, so the grain size became large. As a result, the maximum deviation was large.

[0177] In No. 50, the final solution treatment temperature was low, so the recrystallization was insufficient and the grain size became larger. In addition, since the average rolling load between passes per unit width in the finish cold rolling was large, the accumulated strain became larger and the GROD average value increased. As a result, the bending workability was very poor, and the material broke in the bending test for measuring the maximum deviation.

[0178] In No.51, since the annealing temperature before aging was low, the GROD average value increased and the maximum deviation was large.

[0179] In No. 52, the average rolling load per unit width between passes in the finish cold rolling was large, so the accumulated strain became large and the GROD average value increased. As a result, the maximum deviation was large.

[0180] No. 53 did not undergo the first solution treatment, so the precipitates that exerted the fixing effect were insufficient, and the final solution treatment temperature was high, so the grain size was large. In addition, since the finish cold rolling and pre-aging annealing were not performed, the GROD average value could not be reduced. As a result, the maximum deviation was large.

[0181] No.54 has a low Ti content, so the coarse precipitates that play a fixing effect are insufficient, and the grain size becomes quite large. Along with this, the GROD average value also increases. As a result, the improvement of bending workability is insufficient, and the maximum deviation is large. In addition, due to the low Ti content, the fine precipitates are insufficient and the strength level is low.

[0182] Since the Ti content of No. 55 was high, cracks occurred in the material during hot rolling, and the subsequent steps were stopped.

Claims

1. A copper alloy plate having the following chemical composition, which comprises, by mass%, Ti: 1.00-5.50%, Ag: 0-0.30%, Al: 0-3.00%, B: 0-0.30%, Be: 0-0.15%, Co: 0-1.00%, Cr: 0-1.00%, Fe: 0-1.00%, Hf: 0-1.00%, Mg: 0-1.00%, Mn: 0-1.50%, Mo: 0-1.00%, Nb: 0-1.00%, Ni: 0-1.50%, P: 0 ~0.20%、S:0~0.20%、Si:0~1.00%、Sn:0~1.50%、Ta:0~1.00%、V:0~1.00%、Zn:0~2.00%、Zr:0~1.00%、Total of rare earth elements:0~3.00%、Total of Ag, Al, B, Be, Co, Cr, Fe, Hf, Mg, Mn, Mo, Nb, Ni, P, S, Si, Sn, Ta, V, Zn, Zr and rare earth elements:less than 5.00%、balance is Cu and unavoidable impurities, In the measurement of the measurement area set in the cross section perpendicular to the rolling direction, using EBSD (electron beam backscatter diffraction method) with a step size of 0.05μm, when the boundary with a crystal orientation difference of more than 5° is regarded as the grain boundary, the average grain diameter obtained by using the Area Fraction method is less than 8.00μm, and when the average orientation of the measurement points in the same grain is set as the reference orientation of the grain, the GROD average value, which is the average value obtained by calculating the orientation difference from the reference orientation of the grain to which each measurement point belongs for all measurement points in the measurement area, is less than 7.0°.

2. The copper alloy sheet material according to claim 1, wherein: In the measurement using the EBSD with a step size of 0.05 μm, the KAM value when a boundary with a crystal orientation difference of 5° or more is regarded as a grain boundary is 3.0° or less.

3. The copper alloy sheet material according to claim 1, wherein: The ratio MBR / t of the minimum bending radius MBR and the plate thickness t at which no cracks are generated in the 90° W bending test of BW according to the technical standard JCBAT307:2007 of the Japan Copper and Copper Industry Association is 1.7 or less.

4. The copper alloy sheet material according to claim 1, wherein: The tensile strength in the direction parallel to rolling is 850 MPa or more.

5. The copper alloy sheet material according to claim 1, wherein: The plate thickness is 0.02~0.50mm.

6. The method for producing a copper alloy sheet material according to claim 1, wherein in the production process of performing a first solution treatment, an intermediate cold rolling, a final solution treatment, a finish cold rolling, a pre-aging annealing, and an aging treatment on the intermediate product sheet material in the following order, The first solution treatment is performed under the following conditions: after maintaining the temperature in the range of 750 to 960°C, cooling is performed while maintaining the cooling rate from 750 to 300°C at 3 to 30°C / s, The intermediate cold rolling is carried out under the following conditions: the total rolling rate is 50 to 99%, The final solution treatment is performed under the following conditions: after maintaining the temperature in the range of 730 to 800°C, cooling is performed so that the average cooling rate from 730°C to 300°C becomes 100°C / s or more, Finish cold rolling is performed under the following conditions: the number of rolling passes with a reduction ratio of 15% or more is 0 or more and 3 or less, the total rolling pass average of the rolling load per unit width is 620 kN / m or less, and the total rolling ratio is 3 to 55%, The pre-aging annealing is carried out under the following conditions: the temperature range is 500-700°C for 25-600 seconds, The aging treatment is carried out under the following conditions: maintaining at 300 to 500°C.

7. The method for manufacturing a copper alloy sheet material according to claim 6, wherein: The intermediate product sheet material is a sheet material that is subjected to cold rolling after hot rolling.

8. A current-carrying component using the copper alloy sheet material according to any one of claims 1 to 5 as a material.

9. A heat dissipating component using the copper alloy sheet material according to any one of claims 1 to 5 as a material.

Citation Information

Patent Citations

  • Titanium copper and its production method

    JP2006265611A

  • Method for manufacturing titanium-copper for electronic component

    JP2010261066A

  • Titanium copper, wrought copper product, electronic component and connector

    JP2012012631A

  • Titanium copper

    JP2013204140A

  • High-strength titanium-copper

    JP2014084512A

Cited By

  • Copper alloy, preparation method thereof and elastic electronic component

    CN121700237A